Improving reading competence in aphasia with combined aerobic exercise and phono-motor treatment: Protocol for a randomized controlled trial. - Olga Boukrina; Elizabeth B Madden; Brian M Sandroff; Xiangqin Cui; Abubakar Yamin; Yekyung Kong; William W Graves (PLoS ONE)
Aphasia, a communication disorder caused primarily by left-hemisphere stroke, affects millions of individuals worldwide, with up to 70% experiencing significant reading impairments. These deficits negatively impact independence and quality of life, highlighting the need for effective treatments that target the cognitive and neural processes essential to reading recovery. This Randomized Clinical Trial (RCT) aims to test the efficacy of a combined intervention incorporating aerobic exercise training (AET) and phono-motor treatment (PMT) to enhance reading recovery in individuals with post-stroke aphasia. AET, known for its positive impact on cerebral blood flow (CBF) and oxygenation, is hypothesized to facilitate neuroplasticity when administered before PMT, an intensive therapy aimed at strengthening phonological processing. While most existing treatments focus on spoken language production, this study builds on evidence that PMT can also improve reading skills. The study is structured as a Phase I/II clinical trial and compares the effects of AET plus PMT to a control condition of stretching plus PMT on reading and other language outcomes including naming, auditory comprehension, and spontaneous speech. Additionally, it investigates the immediate and sustained impacts of the intervention on CBF, functional connectivity, and task-evoked brain activity. The central hypothesis posits that AET will increase CBF and, when combined with PMT, will lead to enhanced reading recovery, supporting treatment-induced plasticity. This trial represents one of the first large-scale interventions targeting post-stroke reading impairments and provides critical insights into the potential of combining AET with cognitive rehabilitation to improve language recovery in aphasia.